INTENSITAS SERANGAN PENGGEREK KAYU DI LAUT PADA BEBERAPA JENIS KAYU - Mohammad Muslich; Ginuk Sumarni (Pusat Penelitian dan Pengembangan Hasil Hutan, 1988)
One hundred fifty pieces of wood from five species were exposed to marine borers in three different locations for periods up to three months at different periods. The tests were conducted around Jak9rta Gulf i.e about 3 km off shore from Mauk from January - June 1986, Rambut Island from July - November 1986, and Puntung, Java lsland from November 1986 - February 1987. The result shows that most of the wood tested were badly attacked by Molluscs belonging to the specise Martesia striata Linne., Teredo bartschi Clap., Dichyathifer manni Wright., and Bankia campanellata Molli Roch. Diospyros celebica Bahh, wood seems to be resistant to marine borers. The intensity of borer attack on the woods in the three locations are not significantly different.